Dietary and habitat shifts in relation to climate of Neogene-Quaternary proboscideans and associated mammals of the Indian subcontinent. (15th November 2019) - Patnaik, Rajeev; Singh, Ningthoujam Premjit; Paul, Debajyoti; Sukumar, Raman
Abstract: Several studies have established that African proboscideans shifted their feeding strategies (browsing vs. grazing) in response to climatic and ecological changes. However, similar studies on their Indian relatives are rare. In this regard, we analysed the stable carbon (δ 13 C) and oxygen (δ 18 O) isotope composition, hypsodonty indices (HI), and lamellae numbers of both newly recovered and existing fossil material (proboscideans and associated mammals) spanning the last ∼14 Ma. We also obtained intra-tooth δ 13 C and δ 18 O values of selected extant and extinct proboscideans as well as associated mammals to understand any intra- and inter-annual variation in dietary and water intake behaviour, respectively. Our results reveal that Middle Miocene brachydont deinotheres (ex. Deinotherium indicum ) and bunodont gomphotheres (ex. Gomphotherium ) with few cusp pairs were browsers living in relatively closed forests under moist conditions. By Late Miocene they continued browsing in relatively open forests. Deinotheres in the subcontinent did not survive the Late Miocene climate change that led to drier conditions and the spread of grasslands. The Late Miocene endemic forms Stegolophodon and Stegodon were browsers while the immigrant Choerolophodon was a mixed feeder. However, Pliocene gomphotheres such as bunodont Anancus and brachydont Stegodon adapted themselves to shrinking forests and spreading grasslands; the former sustained on grazing, whereas the latter showed flexibility in its diet ranging from browsing, mixed-feeding to pure grazing. Associated mammals such as rhinoceratids, giraffids, equids, and bovids responded in a similar manner to this climatic and ecological transition across the Late Miocene to Pliocene by shifting their diets accordingly. The Mid-Pliocene hypsodont elephantid immigrant Elephas planifrons, the Early Pleistocene hypsodont immigrant E. hysudricus, and Elephas platycephalus, with multiple lamellae (10–16) were also essentially grazers. Sometime around Middle Pleistocene, the giant elephantid immigrant Palaeoloxodon namadicus, a pure grazer, appeared on the grasslands of the subcontinent, coinciding with a shift in E. hysudricus diet from pure grazing to browsing. E. hysudricus likely gave rise to the extant E. maximus, a mixed feeder with higher contribution of browse to its diet. Highlights: We analysed δ 13 C and δ 18 O values, HI and LN of both newly recovered and existing proboscideans and associated mammals spanning the last ∼14 Ma. Neogene proboscideans from African and Indian subcontinent show overall similar trend in their dietary shift (browsing to grazing). The hypsodont elephantine Elephas planifrons, E. platycephalus and E. hysudricus were all dominantly grazers. Sometime around M.Pleistocene, the immigrant  P. namadicus, likely influenced the shift in the diet of E. hysudricus  from pure grazing to browsing.